The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12864-018-4710-1
|View full text |Cite
|
Sign up to set email alerts
|

Motifome comparison between modern human, Neanderthal and Denisovan

Abstract: BackgroundThe availability of the genomes of two archaic humans, Neanderthal and Denisovan, and that of modern humans provides researchers an opportunity to investigate genetic differences between these three subspecies on a genome-wide scale. Here we describe an algorithm that predicts statistically significant motifs based on the difference between a given motif’s actual and expected distributions. The algorithm was previously applied to plants but was modified for this work.ResultsThe result of applying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Geometric morphometrics studies that compared Homo sapiens and Neanderthals [Bastir et al, 2011, Kochiyama et al, 2018] had already identified that Homo sapiens has significantly larger olfactory bulbs compared to Neanderthals. Cell-cell adhesion also has been found enriched previously in a motif macroanalysis of the Neanderthal and Denisovan genomes [Cserhati et al, 2018]. Cell adhesion is an important process in human-specific cortical folding and apical progenitors cell cycle [Mora-Bermúdez et al, 2016, Wianny et al, 2018].…”
Section: Resultsmentioning
confidence: 98%
“…Geometric morphometrics studies that compared Homo sapiens and Neanderthals [Bastir et al, 2011, Kochiyama et al, 2018] had already identified that Homo sapiens has significantly larger olfactory bulbs compared to Neanderthals. Cell-cell adhesion also has been found enriched previously in a motif macroanalysis of the Neanderthal and Denisovan genomes [Cserhati et al, 2018]. Cell adhesion is an important process in human-specific cortical folding and apical progenitors cell cycle [Mora-Bermúdez et al, 2016, Wianny et al, 2018].…”
Section: Resultsmentioning
confidence: 98%
“…This is because in the normal distribution, 5% of all values lie above 1.96 z -score limit. This cutoff was also used in the k-mer prediction study of modern and archaic humans [3].…”
Section: Methodsmentioning
confidence: 99%
“…These elements are both conserved and diverged across species owing to their functional significance, which enables these k-mer signatures ideal for species identification. Several recent studies have described the distribution of statistically significant k-mers in the genomes and several regulatory subregions (core, proximal, distal promoters, and 3′ and 5′ UTRs) in a small number of plant species as well as modern and archaic humans [13]. A k-mer is a type of short oligonucleotide of length k. K-mers can be part of core segments of transcription factor binding sites or regulatory elements that take part in protein binding and gene regulation in different subregions of the genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A k-mer is unique sub-sequence of nucleotide sequence. The distribution of statistically significant kmers in a genomes and other regulatory subregions has been described in a number of recent studies (Hashim and Abdullah 2015;Cserhati et al 2018). It has also been also employed in comparative studies (Cserhati et al 2019), and major advantages of alignment-free approaches based on k-mer are their speed and ability to remove biases.…”
Section: Bioinformatics Tools Used In K-mer Analysismentioning
confidence: 98%